2017
DOI: 10.1002/ijc.31080
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles isolated from human renal cell carcinoma tissues disrupt vascular endothelial cell morphology via azurocidin

Abstract: Cancer-associated extracellular vesicles (EVs) are intimately involved in establishment of tumor microenvironment and occurrence of metastasis. However, previous studies have mainly relied on experiments with cultured cell lines or mouse models, making it difficult to gain a full understanding of EV functions in human body. Hence, we extracted EVs directly from surgically resected viable clear cell renal cell carcinoma (ccRCC) tissues and adjacent normal renal tissues (n = 20). Quantitative LC/MS analysis iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 38 publications
(76 reference statements)
1
70
0
Order By: Relevance
“…In 2017, Vella et al used frozen human brain tissue to study EVs [31]. More recently, Jang et al studied EVs from metastatic human melanoma and Jingushi et al isolated EVs from human kidney tumors [21,32]. Although Jingushi et al reported successful EV isolation from RCC, we found it necessary to optimize available protocols to reduce non-EV contaminants to acceptable levels.…”
Section: Discussionmentioning
confidence: 96%
“…In 2017, Vella et al used frozen human brain tissue to study EVs [31]. More recently, Jang et al studied EVs from metastatic human melanoma and Jingushi et al isolated EVs from human kidney tumors [21,32]. Although Jingushi et al reported successful EV isolation from RCC, we found it necessary to optimize available protocols to reduce non-EV contaminants to acceptable levels.…”
Section: Discussionmentioning
confidence: 96%
“…Since numerous publications have reported tissue-derived EVs without thorough protein characterization of EV-depleted cellular markers and specific EV subtype markers 12,15,16,[49][50][51][52] , we compared the BH and bdEV proteomes with established EV-related databases. Substantial concordance between our data and the databases was clear (Tabe 3).…”
Section: Discussionmentioning
confidence: 99%
“…In-Gel Digestion [33][34][35][36][37] FASP [38,39] Combined method In-Gel Digestion [28,35,36,[40][41][42][43][44][45][46][47][48][49][50][51] In-Sol Digestion [52][53][54] FASP [51,[55][56][57][58][59] Plasma/ Serum Ultracentrifuge In-Sol Digestion [60] FASP [56] Combined method In-Gel Digestion [43] In-Sol Digestion [44,52] FASP [51,57,58] secreted by MCF7, 30 proteins have been known to participate in breast cancer growth, metastasis, and chemoresistance. The most abundant MDA-MD-231 derived exosomal protein is β-actin, which is frequently used as a housekeeping gene in the exosome.…”
Section: Cell Ultracentrifugementioning
confidence: 99%